Efect of palm oil factory sludge manure on the growth and yield of cabbage - Lukas Sebayang (Jurnal Pertanian Tropik, 2019)
Palm sludge is a source of organic material potential to increase cabbage production. The researchwas conducted at Berastagi Sub Research Institute for Horticulture at 1.230 m above sea level onSeptember 2017 to January 2018. The purpose of this study was to determine the effect of palm oilfactory sludge manuring on cabbage growth and yield. The experiment used Randomized BlockDesign with 5 replications. The results indicated that treatment of NPK + Cattle manure at 30 tons/hawas the highest yield (73.4 tons/ha) followed by treatment NPK + Palm Oil Factory Sludge at 15tons/ha ( 69.6 tons/ha). The used of fertilizer combination of NPK + Palm Oil Factory Sludge at 15tons/ha was recommended.